2021
DOI: 10.1186/s13063-021-05024-y
|View full text |Cite
|
Sign up to set email alerts
|

Missing clinical trial data: the evidence gap in primary data for potential COVID-19 drugs

Abstract: Background Several drugs are being repurposed for the treatment of the coronavirus disease 2019 (COVID-19) pandemic based on in vitro or early clinical findings. As these drugs are being used in varied regimens and dosages, it is important to enable synthesis of existing safety data from clinical trials. However, availability of safety information is limited by a lack of timely reporting of overall clinical trial results on public registries or through academic publication. We aimed to analyse … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…Therefore, the vast majority of RCTs focused on testing the repurposing of already existing drugs that had been already approved or had been under investigation for other indications( 17 ) ( Table 1 ). This is based on the assumptions that there is substantial evidence on the efficacy and safety of these drugs ( 18 ). However, a review focusing on the reporting of clinical results for 19 potential COVID-19 drugs showed that 40% of the completed trials assessing those drugs, prior to the pandemic, did not report their results on ClinicalTrials.gov or in the scientific literature ( 18 ).…”
Section: The Covid-19 Agenda Of Randomized Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the vast majority of RCTs focused on testing the repurposing of already existing drugs that had been already approved or had been under investigation for other indications( 17 ) ( Table 1 ). This is based on the assumptions that there is substantial evidence on the efficacy and safety of these drugs ( 18 ). However, a review focusing on the reporting of clinical results for 19 potential COVID-19 drugs showed that 40% of the completed trials assessing those drugs, prior to the pandemic, did not report their results on ClinicalTrials.gov or in the scientific literature ( 18 ).…”
Section: The Covid-19 Agenda Of Randomized Trialsmentioning
confidence: 99%
“…This is based on the assumptions that there is substantial evidence on the efficacy and safety of these drugs ( 18 ). However, a review focusing on the reporting of clinical results for 19 potential COVID-19 drugs showed that 40% of the completed trials assessing those drugs, prior to the pandemic, did not report their results on ClinicalTrials.gov or in the scientific literature ( 18 ). For hydroxychloroquine, 37% of the trials were unreported.…”
Section: The Covid-19 Agenda Of Randomized Trialsmentioning
confidence: 99%
“…In particular, the duplication of effort has plagued COVID‐19 efforts, especially clinical trials; with, for example, 343 reported clinical trials of hydroxychloroquine as of the end of November 2020 3 . Moreover, across a range of drugs, many of the trials have been too small or poorly designed to answer rigorous questions—with too few being blinded, randomized, controlled trials—and a large proportion of the completed trials have not reported on ClinicalTrials.gov or in the academic literature (1516 of 3754 completed trials, 40.4%) 4 . The large number of vaccine candidates in clinical development is extraordinary, and although some of those multiple efforts are undoubtedly important to ensure success—and reflect an understandable urge to respond quickly to the pandemic—competitive forces have probably driven this number too high, resulting in a potential waste of effort and resources.…”
Section: Industrymentioning
confidence: 99%
“…A report shows that 3754 clinical trials had been completed for COVID-19. It has been noted that some of these clinical trial results had not been updated in trial repositories (Rodgers et al 2021). Quite a few therapeutics have given better results in clinical trials for severe COVID-19 patients Chiranjib Chakraborty and Ashish Ranjan Sharma contributed equally to this work.…”
mentioning
confidence: 99%